Identifikasi Potensi Predator dan Hama pada Peternakan Kelulut (Hymenoptera; Apidae; Meliponini; Tetragonula, Lepidotrigona) melalui Pengamatan Cepat di Kabupaten Padang Pariaman, Sumatera Barat: Identification of Potential Predators and Pests in Stingless Bee Farm (Hymenoptera; Apidae; Meliponini; Tetragonula, Lepidotrigona) through Rapid Observation in Padang Pariaman Regency, West Sumatra - Janra, Muhammad; Herwina, Henny; Salmah, Siti; Rusdimansyah; Jasmi (Departemen Biologi, Institut Pertanian Bogor, 2020)
Stingless bees have been considered as the excellent option in the apiary sector as they produce valuable products such as honey, bee pollen and wax. Apiary business with stingless bee at its core has shown progressive increment especially in West Sumatra. Therefore, to maximize the production of the stingless bee apiary, knowing detrimental predator or pest organisms as well as the way of managing them are essential. This article described potential predators and pests of stingless bee identified through rapid observation conducted on 14 April 2019 at a community apiary in Padang Pariaman Regency, West Sumatra. There were 17 predators and pests identified, consist of six bird species, five odonate species and six ant species. The predation, competition and disadvantage possibly emerge from the existence of these organisms around stingless bee apiary are discussed, along with the feasible mitigation effort.